TZ- VirtIO: Enabling Standardized Inter-Partition Communication in a Trustzone-Assisted Hypervisor - Oliveira, A. (2018)
Virtualization technology allows the coexistence and execution of multiple operating systems on top of the same hardware platform. In the embedded systems domain, virtualization has been focused on the isolation of critical requirements like real-time, security and safety from non-critical characteristics. The strict confinement of guest partitions typically provided by virtualization does not suit the modular and inter-cooperative nature of embedded systems. The need for inter-partition communication has been addressed by multiple virtualization solutions, either to enable guest-level device para-virtualization or to ensure increased flexibility regarding cooperative partitions. However, the majority of existing approaches follow an ad hoc approach with limited to none applicability outside their solution's scope. This paper presents TZ-VirtIO, an asynchronous standardized inter-partition communication (IPC) mechanism on top of a TrustZone-assisted dual-OS hypervisor (LTZVisor). The implemented IPC uses the standard VirtIO transport layer. The experiments conducted on a physical platform show a scalable, high-bandwidth and low-overhead solution for both single-core and multi-core architectures.